Allergen-specific sublingual immunotherapy altered gut microbiota in patients with allergic rhinitis - Wu, Jing; Wang, Dan; He, Wen-Jun; Li, Jun-Yang; Mo, Xi; Li, You-Jin (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionAllergen-specific immunotherapy (AIT) induces long-term immune tolerance to allergens and is effective for treating allergic rhinitis (AR). However, the impact of sublingual immunotherapy (SLIT) on gut microbiota from AR patients and its correlation with treatment efficacy remains unclear.MethodsIn the present study, we enrolled 24 AR patients sensitized to Dermatophagoides farinae (Der-f) and 6 healthy donors (HD). All AR patients received SLIT treatment using standardized Der-f drops. Stool samples were collected from AR patients before treatment, and 1- and 3-months post-treatment, as well as from HD, for metagenomic sequencing analysis.ResultsAR patients had significantly lower richness and diversity in gut microbiota compared to HD, with notable alterations in composition and function. Besides, three months post-SLIT treatment, significant changes in gut microbiota composition at the genus and species levels were observed in AR patients. Streptococcus parasanguinis_B and Streptococcus parasanguinis, which were significantly lower in AR patients compared to HD, increased notably after three months of treatment. LEfSe analysis identified these species as markers distinguishing HD from AR patients and AR patients pre- from post-SLIT treatment. Furthermore, changes in the relative abundance of S. parasanguinis_B were negatively correlated with changes in VAS scores but positively correlated with changes in RCAT scores, suggesting a positive correlation with effective SLIT treatment. DiscussionSLIT treatment significantly alters the gut microbiota of AR patients, with S. parasanguinis_B potentially linked to its effectiveness. This study offers insights into SLIT mechanisms and suggests that specific strains may serve as biomarkers for predicting SLIT efficacy and as modulators for improving SLIT efficacy.